Conceptualizing the Visitor Experience: A Review of Literature and Development of a Multifaceted Model. Issue 2 (2nd July 2016) - Packer, Jan; Ballantyne, Roy
ABSTRACT: Although commonly considered the core product offered by visitor attractions such as museums, zoos, and heritage sites, the visitor experience has proved a difficult construct to both define and measure. This article reviews the concept of visitor experience, drawing from literature in tourism and leisure research as well as museum and visitor studies, and identifies a number of issues on which the literature presents multiple perspectives. By clarifying these issues, this article takes a first step toward building a shared vocabulary to describe and measure visitor experiences. The article presents a conceptual scheme that describes relationships among key factors, and a multifaceted model of the visitor experience that offers a way of characterizing both its content and intensity. The article thus provides a basis for future research designed to capture this elusive phenomenon.